Cycling, car, or public transit: a study of stress and mood upon arrival at work. Issue 1 (6th February 2017) - Brutus, Stéphane; Javadian, Roshan; Panaccio, Alexandra Joelle
Abstract : Purpose: The purpose of this paper is to investigate the impact of various commuting modes on stress and mood upon arrival at work. Design/methodology/approach: Data on stress and mood were collected after 123 employees arrived at work by bike, car, or public transit. In order to account for the natural fluctuation of stress and mood throughout the day, the assessment of the dependent variables was made within the first 45 minutes of arrival at work. Findings: As hypothesized, those who cycled to work were less stressed than their counterparts who arrived by car. However, there was no difference in mood among the different mode users. Practical implications: A lower level of early stress among cyclists offers further evidence for the promotion of active commute modes. Originality/value: This study underscores the importance of being sensitive to time-based variations in stress and mood levels when investigating the impact of commute modes.